Biodegradable Plastic from Cassava Waste using Sorbitol as Plasticizer - Wahyu Rinaldi; Mirna Rahman Lubis; Umi Fathanah (Syiah Kuala University, 2015)
Cassava waste can be utilized as raw material for biodegradable plastics. This research studied the influence of sorbitol, carboxymethyl cellulose (CMC) and the gelatinization temperature in the preparation of biodegradable plastic from cassava waste. 12 gram of starch from cassava waste was stired with 68.2 gram of water-ethanol solution at 75 rpm and is fixed during this study. While the amount of sorbitol, CMC and gelatinization temperature are varied. The best results are showed at 44.90% in water absorption, 101.4 MPa in tensile strength, 76.57% in elongation, 4.17 MPa in Young's modulus, and decomposition time are 64, 67, and 79 days.